Waste Generation potential and Households Willingness to Pay for TPS 3 R Waste Management in Babakan village, Bogor District - Nurpagi, Egi Mariah; Ekayani, Meti; Ismail, Ahyar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Babakan is one of the villages around campus that has the potential to increase household waste, this waste problem is exacerbated by the fact that every year there are new students and residents who live in Babakan. The current waste waste management is using a collection-transport-disposal system which has an impact on decreasing the quality of residential environment. TPS 3R is community-based waste management with the application of Reduce, Reuse, and Recycle towards zero waste, which can be implemented in Babakan. The purpose of this study was to examine the potential of implementing TPS 3R in households in Babakan. The analytical methods used in this research are quantitative descriptive analysis which refers to SNI 19-3964-1994 as a guideline, qualitative descriptive analysis, Contingent Valuation Method, and Benefit analysis.  The result showed that the total pile of household waste, the level of participation, and the household’s willingness to pay for TPS 3R plan made it possible to implement the TPS 3R program. Operational costs for TPS 3R are affordable, although there is the potential for free riders to rise.